Association of lipophilic opioids and hyperbaric bupivacaine in spinal anesthesia for elective cesarean section. Randomized controlled study - Braga,Angélica de Fátima de Assunção (2014)
PURPOSE:To evaluate the efficacy and side-effects of fentanyl and sufentanil combined with hyperbaric spinal bupivacaine in elective cesarean section.METHODS:A prospective, randomized, double-blind study with 64 term parturients, distributed into 2 groups according to the opioid combined with hyperbaric bupivacaine 0.5% (10mg): GF - fentanyl (25µg) and GS - sufentanil (5.0µg). The latency and maximum sensory block level; degree and duration of motor block; duration and quality of analgesia; maternal-fetal repercussions were evaluated. This was an intention-to-treat analysis with a 5% significance level.RESULTS: The latency period, maximum sensory block level, motor block degree and perioperative analgesia were similar in both groups. Motor block and analgesia had a longer duration in the sufentanil group. Maternal adverse effects and neonatal repercussions were similar. The incidence of hypotension was higher in the fentanyl group. In both groups, there was a predominance of patients who were awake and either calm or sleepy.CONCLUSIONS:The addition of fentanyl and sufentanil to hyperbaric subarachnoid bupivacaine was shown to be effective for the performance of cesarean section, and safe for the mother and fetus. Analgesia was more prolonged with sufentanil.